(untitled) (REM. Chilean Journal of Musical Education, 2025)
Several studies point out the importance of the conductor’s gaze for the communication with the musicians during the practice of a work for orchestra (Johnson, et al., 2003; Whitaker, 2011; Poggi, et al., 2020) however, there are no studies that explain why this importance. This ongoing research aims, based on knowledge in the areas of music education and cognition, to determine the factors that justify the importance of the gaze in the communication process between the conductor and the musicians. To this end, we will develop an experiment using an eye-tracker to measure the eye movements of conductors during orchestral performance. These physiological measurements will be complemented by a qualitative analysis of the conductors’ and musicians’ performance through a series of explanatory interviews. From the results obtained, we intend to explain more precisely the role of gaze communication during conductor’s performance in orchestral practice, filling a gap of studies on this subject in the area. The analysis of the results carried out with the device software will also allow us to observe in detail the movement and direction of the gaze of conductors during musical performance, defining the visual communication strategies used by them to help university teachers and conductors in training in the development of their orchestral practices.